The longitudinal influence of the level of executive function development on children’s transcriptional skills: a modern view of A. Luria’s ideas - Oshchepkova, Ekaterina S.; Shatskaya, Arina N.; Kovyazina, Maria S. (Frontiers in Psychology, 2023)
In the realm of Cultural-Historical Theory, A. Luria suggested writing as a model of a complex system of higher mental function, since that function is based on various psycho-physiological mechanisms, including processing of audial and visual information; and as a complex system of the frontal lobe functions of overcoming perseveration, and creation and control of the writing program. Subsequent research on these topics has shown a close association between the level of development of executive functions (EF) and writing skills. Nevertheless, the question of which parts of EF influence which aspects of writing, remains unresolved. In addition, there are few longitudinal studies of EF’s influence on writing. In this article, we focus on the results of a longitudinal study of the influence of EF in children 6.5 years old on their mastery of basic writing skills at the age of 7.3. The results of regression model construction showed that all the aspects of strongly influenced the children’s transcription skills, while the greatest impact on the development of the graphomotor component and spelling skills was exerted by working memory and inhibition control. These results are consistent with studies that have shown a correlation between the development of writing skills and EF. These results also confirm A. Luria’s views on the importance of functions responsible for processing audial and visual information in the process of writing, and the importance of suppressing irrelevant stimuli and perseverations. Our research shows the importance of the development of EF in preschool childhood.